PENGARUH KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP LOYALITAS KARYAWAN - Pratama, Rizqi Yoga; Armanu, Armanu (Jurnal Kewirausahaan dan Inovasi, 2022)
This research aims to analyze the effect of compensation and work environment on employee loyalty at PT XYZ. The type of research is explanatory research with a quantitative approach. Respondents used in this research as many as 54 people using the entire population. The data technique uses a questionnaire which is measured by a Likert scale. Data analysis in this reasearch used multiple linear regression analysis with SPSS software version 20. In this research, the hypothesis was tested using the t test. The results of hypothesis testing indicate that the variables of compensation and work environment have a partial effect on employee loyalty. In addition, the results of the study show that compensation and work environment have a simultaneous effect on employee loyalty of PT XYZ.